2017
DOI: 10.1136/bcr-2017-220733
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome and acute kidney injury induced by malathion toxicity

Abstract: We treated a case of acute kidney injury and nephrotic syndrome after malathion inhalation. A 69-year-old Japanese man presented with oedema 15 days after inhalation of malathion, a widely used pesticide. Serum albumin was 2.4 g/dL, urinary protein 8.6 g/gCr and serum creatinine 2.5 mg/dL. Kidney biopsy revealed tubular cell damage, epithelial cell damage in glomeruli and diffuse foot process effacement in electron microscopy. Acute kidney injury progressed to treatment with dialysis. Renal function recovered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Recently, Yokota et al 2017 reported a case of acute renal injury and nephrotic syndrome in a man 15 days after MAL inhalation, associated with proteinuria, abnormality in serum creatinine, and glomerular and tubular damage. Recovery took about 6 weeks under steroid therapy (Yokota et al 2017). A similar case report of acute renal failure associated with MAL inhalation was previously reported by Albright et al (1983).…”
Section: Malathion-induced Nephrotoxicitysupporting
confidence: 74%
See 2 more Smart Citations
“…Recently, Yokota et al 2017 reported a case of acute renal injury and nephrotic syndrome in a man 15 days after MAL inhalation, associated with proteinuria, abnormality in serum creatinine, and glomerular and tubular damage. Recovery took about 6 weeks under steroid therapy (Yokota et al 2017). A similar case report of acute renal failure associated with MAL inhalation was previously reported by Albright et al (1983).…”
Section: Malathion-induced Nephrotoxicitysupporting
confidence: 74%
“…Histopathologically, MAL treatment induced renal degenerative changes including cloudy swelling and cellular desquamations, as well as swollen and pleomorphic mitochondria (Keadtisuke et al 1989;Al-Attar 2010). It was also found that MAL induces an oxidative stress status in the renal tissues, which mostly accounts for increased lipid peroxidation and depletion of GSH, GPx, catalase, and SOD (Baiomy et al 2015;Coban et al 2015;Yokota et al 2017;Selmi et al 2018).…”
Section: Malathion-induced Nephrotoxicitymentioning
confidence: 96%
See 1 more Smart Citation
“…Due to oxidative stress and negative alterations on antioxidant enzyme activities, the toxic effects of malathion on liver, erythrocytes, reproductive system and kidneys have been investigated in experimental studies (11)(12)(13)(14). In some of these studies, it has been revealed that Malathion shows its harmful effects on kidneys by reduced total renal cell numbers (15), glomerular inflammation (16), histological and functional impairment of renal tubules (17,18), proteinuria (19) and nephrotic syndrome (20). Whether this toxic effect of malathion on the kidneys is caused by the negative effect on the oxidant and antioxidant system has not yet been sufficiently revealed in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 Moreover, studies also reported the harmful effects of Malathion on the different tissues and organs of the body of humans and animals. 10,11 The liver is not only a vital organ but also a chief metabolizing site for the bio-transformation of Malathion and its toxic metabolites. Hepatic tissues are considered to be the most exposed tissues to Malathion toxicity.…”
Section: Introductionmentioning
confidence: 99%